2019
DOI: 10.1016/j.chemosphere.2019.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the need for chemical exposure characterisation in a microplate test system: toxicity screening of sixteen pesticides on two marine microalgae

Abstract: Pesticides used in viticulture create a potential risk for the aquatic environment due to drift during application, runoff and soil leaching. The toxicity of sixteen pesticides and one metabolite were evaluated on the growth of two marine microalgae, Tisochrysis lutea and Skeletonema marinoi, in 96-h exposure assays conducted in microplates. For each substance, concentrations of stock solutions were analytically measured and abiotic assays were performed to evaluate the chemical stability of pesticides in micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 78 publications
0
10
0
1
Order By: Relevance
“…1,2,6,8 Therefore, the actual exposure of the cells to the test substances is often not known and decreases with time, which can lead to reduced toxicity and assay sensitivity. 1,2,9,10 Changes in assay setup affect the losses and thereby alter the toxicity parameter based on nominal concentrations. 11 This hampers comparisons of effect data generated using different in vitro bioassay setups and between different chemicals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,6,8 Therefore, the actual exposure of the cells to the test substances is often not known and decreases with time, which can lead to reduced toxicity and assay sensitivity. 1,2,9,10 Changes in assay setup affect the losses and thereby alter the toxicity parameter based on nominal concentrations. 11 This hampers comparisons of effect data generated using different in vitro bioassay setups and between different chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…The test results are normally based on the nominal concentration of a test chemical added to the culture medium at the start of the test. However, several studies have found that volatile and/or hydrophobic chemicals evaporate from wells, crossover to adjacent wells, sorb to microtiter plates, ,,, and sorb to medium constituents. ,,, Therefore, the actual exposure of the cells to the test substances is often not known and decreases with time, which can lead to reduced toxicity and assay sensitivity. ,,, Changes in assay setup affect the losses and thereby alter the toxicity parameter based on nominal concentrations . This hampers comparisons of effect data generated using different in vitro bioassay setups and between different chemicals. , These exposure issues can limit the applicability, value, and relevance of in vitro toxicological data because even a well-characterized toxicological response is of limited value if it cannot be linked to a well-defined exposure level.…”
Section: Introductionmentioning
confidence: 99%
“…The IV-MBM DP v1.0 model was parameterized and applied to simulate the chemicals and single dose scenarios described in Tanneberger et al (2013) and Dupraz et al (2019) The observations being compared to are the ratios of measured medium concentration at the end of the 24 or 96 h exposure period (C24 or C96) to the initial medium concentration (C0) (i.e., C24/C0 or C96/C0). Cellular concentrations were not measured in these studies.…”
Section: Methodsmentioning
confidence: 99%
“…The chemicals simulated for the Tanneberger et al (2013) study ( n = 27) and the Dupraz et al (2019) study ( n = 13) along with the required property data and initial nominal doses are compiled in the Supplementary Material . The simulated chemicals cover a wide range of hydrophobicity and volatility [e.g., the octanol-water partition coefficient (log K OW ) and the air-water partition coefficient (log K AW ) estimates span more than ten orders of magnitude] and thus are expected to behave very differently in in vitro test systems.…”
Section: Methodsmentioning
confidence: 99%
“…As pointed out in the results section, EC50s determined in culture flasks (supplementary material: Table S6) were two-to six-fold lower than those in microplates, indicating a higher toxicity for exposed microalgae (Table 1 and supplementary material: Table S9). These discrepancies are probably due to the different characteristics of the materials composing microplates and culture flasks (plastic vs. glass), as well as to the different growth endpoints used to assess impacts on growth in the two exposure systems (cell density in culture flasks vs chlorophyll fluorescence in microplates) as previously discussed in Dupraz et al (2019).…”
Section: Toxicity Of Single Substances In Microplates and Culture Flasksmentioning
confidence: 99%